Penyimpangan Prinsip Kerja Sama dalam Naskah Drama Bunga Rumah Makan Karya Utuy Tatang Sontani - Fitria Rahmawati Zain (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
AbstractIn drama scripts, of course there are dialog interactions, these dialogues often bring up various interpretations. In this study, the author will discuss violations and the principles of cooperation contained in the drama â€œBunga Rumah Makanâ€. Inspected with a pragmatic approach and implications for Indonesian language and literature learning materials. The purpose of writing this article is to find out and obtain a description of the implications of the discourse in the play. The type of this research is qualitative. The method used is descriptive analysis method. As a result, the drama script of â€œBunga Rumah Makanâ€ by Utuy Tatang Sontani violated the principles of cooperation, namely the quantity maxim, quality maxim, relevance maxim, and implementation maxim. Deviations found in the drama â€œBunga Rumah Makanâ€ text which arise due to violations of the principle of cooperation consist of different kinds of implicature. The implicature is an implicature that is clear, hateful, seductive, and refusing. This proves that conversations that do not carry out the principle of cooperation will produce implicature in a conversation.Keywords: Drama, the principle of cooperation, maxim